Anaphylaxis to Sunflower Seed with Tolerance to Sunflower Oil: A Case Report - Jin An (Medicina, 2021)
Sunflower seeds (Helianthus annuus) are an uncommon source of allergy; however, some cases of allergy to sunflower seeds have been reported. Sunflower seed sensitization occurs to storage proteins (2S albumins) and lipid transfer proteins (LTPs). A 46-year-old female presented three allergic reactions within minutes of consuming sunflower seeds. A prick-to-prick test indicated a positive reaction only to sunflower seeds and a negative reaction to other nuts, such as almond, hazelnut, pistachio, cashew, peanut, macadamia, sesame, and walnut. Prick-to-prick and oral provocation tests of sunflower oil were performed, and a negative result was obtained. The patient was prescribed a 0.3 mg epinephrine autoinjector device for emergency intramuscular administration. The patient is currently under avoidance of sunflower seed but eats food cooked in sunflower seed oil. Based on this case, we should recognize that sunflower seeds have the potential to cause severe anaphylaxis, which indicates tolerance to sunflower oil. An accurate and fast diagnosis allows timely recommendation to practice strict avoidance of sunflower seeds, thus reducing the possibility of recurrence of an anaphylactic reaction.